Housing Tradition in Valjevska Podgorina: Ethnologic and Ethnolinguistic Aspects - Ivanović Barišić, Milina M.; Radovanović, Dragana I. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Housing tradition is an important aspect of life in the country. It reflects the living standard of the household, personal attitudes towards the living space and the ways to furnish it. The paper analyses important aspects of the housing tradition and organization of life within the households in Valjevska Podgorina. The inventory of lexemes, terms related to house and household, bears testimony to a traditional culture that combines a variety of historical, ethnocultural, and linguocultural elements and factors.
Keywords: traditional culture; housing tradition; traditional house building; agricultural buildings; linguoculturology; Šumadija-Vojvodina dialects; Valjevska Podgorina